When H II regions are complicated: considering perturbations from winds, radiation pressure, and other effects - Geen, Samuel Thomas; Pellegrini, Eric William; Bieri, Rebekka; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2020)
We explore to what extent simple algebraic models can be used to describe H II regions when winds, radiation pressure, gravity, and photon breakout are included. We (a) develop algebraic models to describe the expansion of photoionized H II regions under the influence of gravity and accretion in power-law density fields with ρ ∝ r−w, (b) determine when terms describing winds, radiation pressure, gravity, and photon breakout become significant enough to affect the dynamics of the H ii region where w = 2, and (c) solve these expressions for a set of physically motivated conditions.
Advance access publication 2019 December 11
Gesehen am 09.04.2020